Prenatal methamphetamine—impact on the mother and child—a review. (25th April 2021) - Perez, Fatima Anne; Blythe, Stacy; Wouldes, Trecia; McNamara, Kelly; Black, Kirsten I.; Oei, Ju Lee
Abstract: Methamphetamine (MA) is the second most commonly used illicit drug in the world, after cannabis. There are limited data on the outcomes of pregnant MA users but there is rapidly emerging evidence to suggest that they are more vulnerable, marginalized and impoverished compared with other drug‐using mothers. MA use during pregnancy is associated with worse pregnancy outcomes and significantly higher rates of co‐existing health and psychosocial problems. Newborn infants exposed to MA are at increased risk of perinatal complications, present differently at birth to infants exposed to other drugs of dependency such as opioids and have poorer neurological adaptation and feeding difficulties. Sparse literature from neuroimaging and cohort studies suggests that the neurocognitive deficits in MA exposed children persist, even into adulthood. Current clinical practice guidelines for the care of substance exposed pregnant women are opioid‐centric with little attention paid to the consequences of prenatal MA exposure.